2000
DOI: 10.1128/.68.11.6215-6222.2000
|View full text |Cite
|
Sign up to set email alerts
|

Neisseria gonorrhoeae Porin Modifies the Oxidative Burst of Human Professional Phagocytes

Abstract: A hallmark of infection with the gram-negative bacterium Neisseria gonorrhoeae is the local infiltration and subsequent activation of polymorphonuclear neutrophils. Several gonococcal outer membrane proteins are involved in the interaction with and the activation of these phagocytes, including gonococcal porin, the most abundant protein in the outer membrane. Previous work suggests that this porin plays a role in various cellular processes, including inhibiting neutrophils activation and phagosome maturation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…Phagocytosis by innate immune cells is a multi‐step process, which involves microbe recognition and ingestion by neutrophils and subsequent degradation by generating ROS and other digestive enzymes. The sequential production of ROS due to bacterial and neutrophil interaction is collectively known as an oxidative burst (Lorenzen et al ., 2000; Roos et al ., 2003; Nauseef, 2007). Bacterial polysaccharides produced by B. cenocepacia and Staphylococcus aureus also prevent phagocytosis and killing by immune cells (Karakawa et al ., 1988; Thakker et al ., 1998; Kampen et al ., 2005; Saldias et al ., 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Phagocytosis by innate immune cells is a multi‐step process, which involves microbe recognition and ingestion by neutrophils and subsequent degradation by generating ROS and other digestive enzymes. The sequential production of ROS due to bacterial and neutrophil interaction is collectively known as an oxidative burst (Lorenzen et al ., 2000; Roos et al ., 2003; Nauseef, 2007). Bacterial polysaccharides produced by B. cenocepacia and Staphylococcus aureus also prevent phagocytosis and killing by immune cells (Karakawa et al ., 1988; Thakker et al ., 1998; Kampen et al ., 2005; Saldias et al ., 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Although we do not currently know the identity of the Gc suppressive factor, one possibility is that ROS production in PMNs is modulated by Gc porin, which has been shown to translocate from the bacterial surface into eukaryotic plasma and internal membranes (Massari et al, 2003). Intriguingly, Lorenzen et al have shown that purified Gc porin inhibits the oxidative burst of PMNs, but in other studies, porin had no effect on PMN oxidative metabolism (Bjerknes et al, 1995;Bauer et al, 1999;Lorenzen et al, 2000). We are exploring whether porin and other Gc products play a role in suppression of the PMN oxidative burst in this system.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, Lorenzen et al . have shown that purified Gc porin inhibits the oxidative burst of PMNs, but in other studies, porin had no effect on PMN oxidative metabolism (Bjerknes et al ., 1995; Bauer et al ., 1999; Lorenzen et al ., 2000). We are exploring whether porin and other Gc products play a role in suppression of the PMN oxidative burst in this system.…”
Section: Discussionmentioning
confidence: 99%
“…Primary granules contain the majority of oxygenindependent PMN antimicrobial components (Faurschou and Borregaard, 2003). Of these components, Gc is resistant to a-defensins (Qu et al, 1996) and suppresses the PMN oxidative burst, which provides the substrate H 2O2 for MPO activity (Britigan et al, 1988;Bjerknes et al, 1995;Lorenzen et al, 2000;Seib et al, 2005;Criss and Seifert, 2008;Wu et al, 2009). However, primary granule proteases, specifically the serine protease cathepsin G, display antigonococcal activity in vitro (Rest, 1979;Casey et al, 1985;Shafer et al, 1986a;Rock and Rest, 1988).…”
Section: Protease Activity Contributes To the Anti-gc Activity Of Phamentioning
confidence: 99%
“…These findings indicate that Gc has evolved mechanisms to resist PMN killing (Johnson and Criss, ). We and others have shown that Gc suppresses the ability of PMNs to produce ROS, and virulence factors that defend the bacteria against oxidative damage do not contribute to Gc survival in PMNs (Britigan et al ., ; Bjerknes et al ., ; Lorenzen et al ., ; Seib et al ., ; Criss and Seifert, ; Wu et al ., ). Thus Gc survival after exposure to PMNs is primarily due to the bacteria resisting oxygen‐independent PMN antimicrobial activities.…”
Section: Introductionmentioning
confidence: 99%